RELATIONSHIP BETWEEN EMOTIONAL MATURITY AND ABILITY TO SOCIALIZE IN ACTIVE STUDENTS IN ORGANIZATIONS IN THE FACULTY OF DAKWAH AND COMMUNICATION UIN RADEN FATAH PALEMBANG - Dwiyana, Melati; Noviza, Neni; Putra, Belajanare (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
The study aims to see how the relationship between emotional maturity and socialization skills with the limitations of this research problem focuses on students who are active in organizations at the Faculty of Da’wah and Communication UIN Raden Fatah Palembang. The research method used is quantitative descriptive with data collection techniques in the form of questionnaires, observation and documentation. The research sample amounted to 72 out of 155 student populations who were active in organizations in the Student Executive Board of the Faculty of Da’wah and Communication which was calculated using the Slovin formula with an error tolerance of 5%. The results of the study showed that that the results of the relationship between emotional maturity and socialization skills showed an r count of 0.593, p = 0.000 (p < 0.05). The conclusion is that emotional maturity and socialization skills in students who are active in organizations at the Faculty of Da’wah and Communication UIN Raden Fatah Palembang are in the “moderate” category. Then, between emotional maturity and socialization skills there is a positive relationship with a moderate level of closeness.